College males’ behaviors, intentions, and influencing factors related to vaccinating against HPV - Koskan, Alexis (Hum Vaccin Immunother, 2020)
In the US, individuals between ages 18 and 26 have the highest incidence of new human papillomavirus (HPV) infections, the most common sexually transmitted infection worldwide. HPV infection can cause genital warts, and persistent infection with cancerous strains can develop into multiple types of cancers. In 2011, the Centers for Disease Control and Prevention recommended that both men and women receive the vaccine. However, young adult men, including college-aged men, have been slow to initiate and complete the vaccine series. Our cross-sectional study, guided by the Theory of Planned Behavior, explores college men’s vaccination uptake and series completion behaviors and their intentions to vaccinate. Using logistic regression, we examined how students’ attitudes, perceived behavioral control, and subjective norms impacted their HPV vaccine–related behaviors and intentions. Subjective norms, followed by perceived behavioral control to communicate with a provider about the HPV vaccine, had the largest impact on students’ HPV vaccine uptake and completion behaviors and intentions to vaccinate. Both subjective norms and positive attitudes about the vaccine impacted students’ intentions to vaccinate against HPV. Based on these findings, we make various recommendations including campus interventions and policies that could increase HPV vaccine uptake and completion behaviors among college men.